On higher-order boundary value problems by using differential transformation method with convolution terms - Kilicman, Adem; Altun, Omer (Elsevier, 2014)
In this paper, we study higher-order boundary value problems for higher-order nonlinear differential equations having convolution terms. We extend and prove some theorems for nonlinear differential equations by using the differential transform method.